New analytical Solutions of (3+1)-dimensional Shallow Water Wave equation (SWW) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we have obtained new analytical solutions of (3+1)-dimensional SWW equation with Kudryashov method. The study of Shallow water wave equation plays an imperative role in wave theory. For calculation software Maple is used. The solutions obtained by this method are new.